Effects of distributed practice on the proceduralization of morphology. (March 2017) - Suzuki, Yuichi; DeKeyser, Robert
The present study aimed to examine whether distributed practice works better than massed practice for proceduralization of grammatical knowledge. Learners of Japanese as a second language were trained on an element of Japanese morphology under either massed or distributed practice conditions. Results showed that massed practice led to accurate utterances to the same extent as distributed practice. It was also shown that massed practice may lead to more rapid utterances than distributed practice. A number of potential factors that mediate the effects of distributed practice are discussed.